FEATURES OF ORGANIZATION OF LOCAL TAXATION IN FOREIGN COUNTRIES - Voloshchuk , R.Ye. (The actual problems of regional economy development, 2018)
In the article the foreign experience of organization of local taxation is generalized and the tax powers of local self-government bodies are described. The practice of establishing and collecting local taxes and fees in the United Kingdom, Spain, Italy, Germany, Poland, France and Sweden is considered. As a result of the study, it was found that each country has its own national peculiarities in the field of local taxation. Scientific novelty is related to the definition of the characteristic features and methods of establishment and collection of local taxes and fees in foreign countries. The practical significance is reduced to isolate the positive experience of developed countries, which can be used to increase the efficiency of the organization of local taxation in Ukraine.